Encyclopedia of abortion in the United States - Palmer, Louis J., Jr., 1956-; Palmer, Xueyan Z., 1964-; Palmer, Louis J., Jr., 1956- (Jefferson, N.C. : McFarland & Co., 2009)
"This acclaimed encyclopedia, now revised and updated, comprehensively covers abortion from the founding of the nation to the present day. The entries address the many political, legal, social, religious, and medical issues associated with abortion. The roles of the Supreme Court and other judicial and legislative bodies are covered in great detail"--Provided by publisher.
Includes bibliographical references (p. 605-607) and index.
Keywords: Abortion -- United States -- Encyclopedias